"Visual Expressiveness" in Camera-Based Research and Communication. Issue 3 (27th May 2021) - Pauwels, Luc
Abstract : "Visual Expression, " understood here as the purposeful application of formal parameters of a medium to produce meaning, constitutes a crucial element of a (more) visual social science that seeks not only to produce visual records of culture and society, but also strives to communicate disciplinary informed/grounded findings, insights and arguments in a partly visual and multimodal manner. This article discusses and exemplifies the pivotal role of "expression" and "expressiveness" as closely intertwined with aesthetics and the predicative power of (visual) "form" in visual research and communication.